Comparison of Geopolitical, Regional and Funding Differences of Universities in Nigeria, Based on Citations per Paper, Using Web of Science and Scopus - Hilary Okagbue; Anita Az-Abiaziem; Jaime Teixeira da Silva (International Journal of Information Science and Management, 2024)
Extant studies have focused on exploring the research output of universities in Nigeria, but the measure of the quality of research output using citations per paper (CPP) from the Web of Science (WoS) and Scopus is scarcely discussed. This paper investigated the quality of papers published by the top 76 universities in Nigeria. Five hypotheses on CPP were tested using Kruskal-Wallis and Mann-Whitney tests. These hypotheses tested whether CPP is the same or different i) across six geo-political regions (GPRs), ii) between the two major regions, iii) across three university funding types, iv) in Scopus and WoS, and v) if these two databases are correlated. Results using these two databases indicated that no significant median differences were detected among universities across the six GPRs, between northern and southern Nigeria, and between the three funding types (federal, state, and private). Moreover, no significant median differences in CPP between Scopus and WoS were detected, and CPP in both databases was highly positively correlated (0.879; p = 0.05). A comparison of the mean CPP of Nigeria (5.90) from Scopus with 57 other African countries ranked it 47th despite being ranked third in terms of volume of published articles. Policy prescriptions are made on the implications of using CPP for practice.